2022
DOI: 10.15585/mmwr.mm7146a3
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Variation in Early Uptake of COVID-19 Vaccine and Parental Intent and Attitudes Toward Vaccination of Children Aged 6 Months–4 Years — United States, July 1–29, 2022

Abstract: COVID-19 vaccines are safe and effective for infants and young children, and on June 18, 2022, CDC recommended COVID-19 vaccination for infants and children (children) aged 6 months-4 years (1,2). As of November 9, 2022, based on administrative data reported to CDC,* 5.9% of children aged <2 years and 8.8% of children aged 2-4 years had received ≥1 dose. To better understand reasons for low coverage among children aged <5 years, CDC analyzed data from 4,496 National Immunization Survey-Child COVID Module (NIS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Moreover, clear steps on how schools are planning to reduce COVID-19 risks, along with up-to-date safety and effectiveness data on vaccines, may help convince parents who do not want to vaccinate their children. 31,32 Finally, our analysis highlights the interesting role children have in the vaccination decision making process. While some parents/guardians made the choice to vaccinate their children, our results show that a number of parents/guardians considered their children's perspectives and supported their child's independent decisions.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Moreover, clear steps on how schools are planning to reduce COVID-19 risks, along with up-to-date safety and effectiveness data on vaccines, may help convince parents who do not want to vaccinate their children. 31,32 Finally, our analysis highlights the interesting role children have in the vaccination decision making process. While some parents/guardians made the choice to vaccinate their children, our results show that a number of parents/guardians considered their children's perspectives and supported their child's independent decisions.…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, clear steps on how schools are planning to reduce COVID-19 risks, along with up-to-date safety and effectiveness data on vaccines, may help convince parents who do not want to vaccinate their children. 31 , 32 …”
Section: Discussionmentioning
confidence: 99%
“…Among children aged 5 to 11 years who have received at least 1 dose of COVID-19 vaccine as of June 2022, 37% were vaccinated in a pharmacy, and 8% were vaccinated in a school-located vaccination clinic; fewer children aged <5 years with at least 1 dose have been vaccinated in either a pharmacy or school in the first month of vaccine availability (15.0% and 0.3%, respectively, as of July 2022). 11,12 Many pharmacies do not offer vaccine to children aged <5 years, and most that do offer vaccine only to those aged 3 years or older due to legal restrictions and other considerations. 13 Therefore, it is likely that young children will continue to be vaccinated in traditional medical settings such as doctor's office, underscoring the importance of the VFC provider network.…”
Section: Discussionmentioning
confidence: 99%
“…16 A recent report suggests that a lower proportion of parents of unvaccinated children aged <5 years had received a provider recommendation for COVID-19 vaccination than parents of vaccinated children. 12 Even if providers do not offer COVID-19 vaccine on site, their strong recommendation and willingness to engage in discussions with parents/caregivers to address parental questions and concerns is critical. Training and materials that are designed to help providers feel confident in discussing COVID-19 vaccination with parent/caregiver are readily available.…”
Section: Discussionmentioning
confidence: 99%
“…By using the SVI, communities can better understand weaknesses and strengths in their communities so public health officials and emergency response planners can more efficiently allocate vital resources to their communities ( 25 ). The CDC and other peer-reviewed studies suggest that by utilizing the insights provided by the SVI to identify counties with low vaccination rates, state and local governments can prioritize their efforts and allocate funds toward regions that are most in need of the COVID-19 vaccine ( 15 , 17 19 ). Within these studies, some specific actions that can be taken to address inequities revealed by the SVI are community outreach programs, transmitting culturally relevant information to communities, teaming up with trusted messengers to provide accurate and timely information to communities, and ensuring accurate and timely supply of COVID-19 vaccines to communities ( 15 , 17 19 ).…”
Section: Discussionmentioning
confidence: 99%